Burn notice. Season seven [videorecording (DVD)] - Nix, Matt (2013)
Separated from his friends and family, and on the verge of losing it all, Michael Westen goes deep undercover, joining forces with a mysterious woman and infiltrating a sinister terrorist network. With time running out, Michael must do whatever it takes to stay alive and protect his loved ones. But now, he may be forced to go too far.